OPERATIONAL PLANNING OF THE PROCESS OF TRANSPORT MAINTENANCE OF COMBAT AIRCRAFT AT UKRAINIAN AIRFIELDS - Kalinichenko, O.; Pavlenko, O.; Soldatenko І. (Municipal economy of cities. Series: «Economy science», 2022)
The article analyzes the current state and prospects of development of transport service systems for combat aircraft, which allowed to form the purpose of the study in this research. The chosen topic is very relevant, because the rational technology of operational planning of transport service process of combat aircraft allows to increase the efficiency of Ukrainian airports in the current martial law conditions. One of the directions of service cost reduction is the determination of optimum distribution of transport resources for aircraft preparation. It is established that in scientific works considerable attention was paid to the development of airport infrastructure, both military and civil, solution of tasks of effective use of information resources and training of airport personnel, tasks of operational planning at the level of determination of limited technology of systems maintenance, use of digital technologies and construction of models of reliable systems of aircraft transport service. The technological process of transport maintenance of combat aircraft is presented, taking into account the resources involved and the sequence of operations. The process of operational maintenance planning of combat aircraft for maintenance, refueling and ammunition is formalized. According to this process, it is possible to establish the level of influence of the process parameters (the number of resources involved and aircraft serviced) on the evaluation criterion - total costs. Determination of the limitation for the use of available resources with the establishment of the optimal level. An algorithm for determining the optimal number of transport resources, taking into account the conditions of combat aircraft preparation (normal, preliminary preparation and others), the influence of environmental conditions (temperature, time of day), and changes in the normative values of individual resources, is constructed. In accordance with the established sequence of actions, the effectiveness of using the existing technology and the proposed - modular technology, according to certain technological indicators for planning the production process is determined.